EKRANISASI NOVEL SURGAYANGTAKDIRINDUKAN KARYA ASMA NADIA KE FILM SURGAYANGTAKDIRINDUKAN KARYA SUTRADARA KUNTZ AGUS - Dina Yati Putri Buana Zulfardi D (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The transfer of the novel into a movie will lead to changes. That's because the process of makingthe novel and the film are very different. Different processes will produce somewhat different resultsjuga.Dalam movie without explaining to the audience what was happening, the audience itself hasbeen understood through movement and images shown, while in the novel the reader to imagineexempted in accordance with what they think. To bridge the misunderstanding of society (lovers ofliterature) to the film adaptation of the literary work (novel), this research needs to be done. This is sothat people can see the film as a film without overshadowed by his literary work (novel).This study aimed to: describe the novel ekranisasi Surga yang Tak Dirindukan Asma Nadia worksinto films by director Kuntz Agus Surga yang Tak Dirindukan.This study is a qualitative study usingdescriptive methods. Data of this study is novel Heaven episode story that Asma Nadia Tak missedwork and the film Heaven Not missed by director Kuntz Agus. Data was collected through three stages,namely; The first step is to read the novel Heaven is not missed work Asma Nadia, followed bywatching the movie Heaven Not missed by director Kuntz Agus. Phase Two is the inventory, to identifyelements of the novel and the film Heaven is not missed.The third phase is the classification of data into the data format. The data validation techniquesdetailed description of the technique. Analyzing technique is done with the theory ekranisasi. Based onthe results of the study, concluded the following. First, a reduction in part ceritan novel Heaven AsmaNadia Tak missed work in the film Heaven is not missed by director Kuntz Agus. Secondly, there wasan additional episode in the story in the film Heaven is not missed by director Kuntz Agus. Third, thereis a change of variety of events, characters and background story episode in the film Heaven is notmissed by director Kuntz Agus. Subtraction, addition and alteration variation on the novel and the filmHeaven There may be missed characters, plot and setting. Such changes may result in changes ofmeaning and story standpoint.